Enhancing Speaking Skills through English Conversation Content on TikTok: EFL Students’ Practices and Perceptions - Sari, Widiya Permata; Agustina, Shafa Amelia; Maharani, Lintang Dwi; Nazarrina, Nazia; Eviyuliwati, Ismalianing; Hidayat, Didin Nuruddin; Zakila Mardatila Ersyad (Institut Agama Islam Negeri Palopo, 2024)
As a social media platform, TikTok has a lot of features that draw users in and may help students improve their knowledge and foreign language proficiency, especially in speaking. The purpose of the study was to find out how students utilized TikTok's English Conversations content to improve their speaking abilities and how they felt about the platform as a learning tool. A qualitative descriptive approach was employed in the study. Research instruments such as questionnaires and interviews were used to gather data from 13 individuals. Additionally, a thematic and descriptive analysis was used to collect the data. The results of the study revealed that 12 of the 13 participants were frequent TikTok users who utilized the platform for both learning and fun. In addition, 12 respondents said that the English Conversations material on TikTok enhanced their speaking abilities when questioned about the use of the content and its impact on speaking abilities. The study did identify several difficulties that the students had while using TikTok as a learning tool, though, including the fact that they were easily distracted by entertainment material, that the learning information needed to be more visually appealing, and that the length of the content was excessive. In order to facilitate comparisons, future research might benefit from the use of alternative instruments with bigger sample numbers. These studies may provide additional theories to evaluate if the results support the conclusions of the present inquiry.